Evaluation of Tools and Techniques for the Generation of Warning Alerts: A Survey Paper - Ghaffar, Abid; Ridza Wahiddin, Mohamed; Fauzan Noordin, Mohamad; Shaikh, Asadullah (Transactions on Engineering and Computing Sciences, 2015)
Quality assurance is a key factor for the improvement of an organisational behaviour. It is quite challenging to enhance an organisational performance without realising internal errors and mistakes done by its employees. We have also experienced that most of the security solutions are unsuccessful wherever human behaviour is involved. Organisations sometimes pay huge cost for its survival especially when human error is untraceable and misleading. Online survey has been conducted from different professionals serving at different positions in different organisations. Variety of multi-agent system tools (MAS) is available in the market for modelling and simulation of human behaviour. Brahms modelling and simulation tool has been selected among different multi-agent system tools due to its distinguished features to detect human errors in an organisation which supports warning alert generation system.